PERANCANGAN APLIKASI SISTEM PEMBAYARAN SUMBANGAN PEMBINAAN PENDIDIKAN PADA SEKOLAH DASAR ISLAM TERPADU AL KALAM DEPOK BERBASIS JAVA - Anindia Bella Amalia Rizki; Nahot Frastian; Randi Ramliyana (JISAMAR (Journal of Information System, Applied, Management, Accounting and Research), 2023)
The purpose of planning this application system is to help improve the quality of service in paying donations for coaching at SDIT Al Kalam, as well as raising this issue as research material, the authors also design a system that can help facilitate the process of paying donations for educational development. With this application, administrative operators can see only payments for education coaching donations that have been paid and can make it easier and more efficient to recapitulate payments for education coaching donations at SDIT Al Kalam. Based on the discussion that has been described, the conclusions obtained from making the payment application for education development donations are that the application of a payment information system can help convey payment information more effectively and efficiently and the application of a payment system for educational development donations can produce accuracy in data processing, so that it is more improve the accuracy and correctness of the information generated in the preparation of reports.